A surgeon's assessment of inadequate neuromuscular antagonism in a case of prolonged neuromuscular blockade - James J Lamberg; Joseph F Answine (Wolters Kluwer Medknow Publications, 2013)
Evaluation of the degree of neuromuscular blockade by the surgeon using clinical criteria alone is unreliable. We report a case of prolonged neuromuscular blockade lasting 5.5 h, where an additional intra-operative dose of neuromuscular relaxant was given at the request of the surgical team. Possible causes of prolonged neuromuscular antagonism are discussed, as is the importance of neuromuscular assessment prior to the administration of additional neuromuscular blocking agents when receiving a surgeon request for additional neuromuscularblockade.